Improving The Quality and Effectiveness of Treatment of Patients with Dental Anomalies - U.G’. Nusratov; L. Yu. Matrizayev (Genius Publishing Group, 2022)
Improving the quality and effectiveness of treatment of patients with dental anomalies by improving the activities of dental technicians in modern conditions. It consists in the fact that the data of timekeeping and calculation of material consumption can be used in practical healthcare to calculate the norms of time in the manufacture of removable orthodontic devices; determining the cost of laboratory stages of their manufacture; the cost of orthodontic devices.
Keywords: Dental Anomalies; The Activities Of Dental Technicians; Removable Orthodontic Devices